Kinetics and Oxidation of Substituted Benzyl Alcohols by Phenyliodoso Acetate - R. Girija; S. Aruna (E-Journal of Chemistry)
Oxidation of benzyl alcohol and some meta- and para- substituted alcohols by phenyliodoso acetate (PIA) in t-butyl alcohol–water medium (50:50) leads to the formation of corresponding benzaldehyde. The stoichiometry of the reaction was found to be 1:1. The reaction was first order each in substrate and oxidant concentrations. This reaction was studied at four different temperatures and the activation parameters were calculated. Correlation analysis was carried out using Taft’s and Swain’s dual substituent parameter (DSP) equation. The rate data of meta- compounds showed good correlation with (F,R) values, para-substituted benzyl alcohols showed good correlation with σIσR+ A suitable mechanism has been proposed.